Hantzsch Esters as Multifunctional Reagents in Visible-Light Photoredox Catalysis - Huang, Wenhao; Cheng, Xu (Synlett, 2017)
Hantzsch esters are used extensively in photoredox catalysis as terminal reductants, donating an electron and a hydrogen atom. They generally exert their reducing potential by means of single-electron transfer to a photoredox catalyst, which acts as an electron shuttle. Recently, they were found to effect single-electron transfer upon visible-light irradiation in the absence of a photocatalyst. We found that this ability could be used for debromination of vicinal dibromo compounds to afford alkenes, as well as for hydrodifluoroacetamidation reactions. We also found that substituted Hantzsch esters could be used as reductive alkylation reagents to build highly congested ketones.
Keywords: Hantzsch ester; photoredox; photoreductive; visible light; hydrogen-atom transfer